Palmitoylated prolactin-releasing peptide treatment had neuroprotective but not anti-obesity effect in fa/fa rats with leptin signaling disturbances - Mráziková, Lucia; Hojná, Silvie; Pačesová, Andrea; Hrubá, Lucie; Strnadová, Veronika; Neprašová, Barbora; Železná, Blanka; Kuneš, Jaroslav; Maletínská, Lenka (Nutrition & diabetes, 2022)
BACKGROUND/OBJECTIVE: Anorexigenic palmitoylated prolactin-releasing peptide (palm11-PrRP) is able to act centrally after peripheral administration in rat and mouse models of obesity, type 2 diabetes mellitus and/or neurodegeneration. Functional leptin and intact leptin signaling pathways are necessary for the body weight reducing and glucose tolerance improving effect of palm11-PrRP. We have previously shown that palm11-PrRP31 had glucose-lowering properties but not anti-obesity effect in Koletsky rats with leptin signaling disturbances, so improvements in glucose metabolism appear to be completely independent of leptin signaling. The purpose of this study was to describe relationship between metabolic and neurodegenerative pathologies and explore if palm11-PrRP31 could ameliorate them in obese fa/fa rat model with leptin signaling disruption. SUBJECT/METHODS: The fa/fa rats and their age-matched lean controls at the age 32 weeks were used for this study. The rats were infused for 2 months with saline or palm11-PrRP31 (n = 7-8 per group) at a dose of 5 mg/kg per day using Alzet osmotic pumps. During the dosing period food intake and body weight were monitored. At the end of experiment the oral glucose tolerance test was performed; plasma and tissue samples were collected and arterial blood pressure was measured. Then, markers of leptin and insulin signaling, Tau phosphorylation, neuroinflammation, and synaptogenesis were measured by western blotting and immunohistochemistry. RESULTS: Fa/fa rats developed obesity, mild glucose intolerance, and peripheral insulin resistance but not hypertension while palm11-PrRP31 treatment neither lowered body weight nor attenuated glucose tolerance but ameliorated leptin and insulin signaling and synaptogenesis in hippocampus. CONCLUSION: We demonstrated that palm11-PrRP31 had neuroprotective features without anti-obesity and glucose lowering effects in fa/fa rats. This data suggest that this analog has the potential to exert neuroprotective effect despite of leptin signaling disturbances in this rat model.
Keywords: Insulin; leptin; Glucose; inzulin; Obesity; obezita; Diabetes Mellitus, Type 2; glukosa; diabetes mellitus 2. typu; Prolactin-Releasing Hormone; Body Weight; krysa rodu Rattus; tělesná hmotnost; Animals; zvířata; Rats; myši; hormon uvolňující prolaktin; Mice; Leptin